2004
DOI: 10.1097/00004872-200403000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Office compared with ambulatory blood pressure in assessing response to antihypertensive treatment

Abstract: The effect of antihypertensive treatment is greater on office blood pressure than on ABP, and is unevenly distributed between day and night. This suggests caution when interpreting trials on cardiovascular protection by antihypertensive treatment that are based only on office blood pressure readings, and advocates a more systematic adoption of ABP monitoring in these trials. The conflicting data provided by the main HOPE study and by the HOPE-ABP monitoring substudy on the role of blood pressure reduction in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
107
1
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(129 citation statements)
references
References 66 publications
11
107
1
10
Order By: Relevance
“…33 We could not evaluate the effects of diuretics on dipping status, 34,35 because 85% of patients were using diuretics at baseline. Third, it has been noted that antihypertensive therapy can have differential affects on day and night BP 36 ; however, the magnitude of the difference is small and unlikely to explain the high prevalence of nondipping in our study. Finally, because the analyses are cross-sectional, we cannot draw causal links between any BP index and target organ damage.…”
Section: Discussioncontrasting
confidence: 57%
“…33 We could not evaluate the effects of diuretics on dipping status, 34,35 because 85% of patients were using diuretics at baseline. Third, it has been noted that antihypertensive therapy can have differential affects on day and night BP 36 ; however, the magnitude of the difference is small and unlikely to explain the high prevalence of nondipping in our study. Finally, because the analyses are cross-sectional, we cannot draw causal links between any BP index and target organ damage.…”
Section: Discussioncontrasting
confidence: 57%
“…In a meta-analysis of studies analyzing the effect of antihypertensive drugs on both office and 24-hour ambulatory BP, the effect on the reduction of 24-hour ambulatory BP was smaller than that in the office because of substantially less reduction in nighttime as compared with daytime BP. 30 Patients in HTN-Japan had a lower body mass index and, perhaps related to this, were less likely to have a history of obstructive sleep apnea compared with patients in SYMPLICITY HTN-3. Asian patients on average have a lower body mass index and have different associations between body mass index, body fat percentage, and health risks compared with an American population.…”
Section: P=0004mentioning
confidence: 96%
“…The genetics of ambulatory BP (ABP) may differ, however, because it is unaffected by the "white-coat" effect. 6 The added value of ABP measurements is best illustrated by studies showing that ABP is a better predictor of target organ damage, 7 cardiovascular morbidity, and mortality 8,9 than conventional office BP.To date, only 4 twin studies 10 -13 and 1 family study 14 reported heritability estimates for daytime or 24-hour ABP. Estimates ranged from 22% to 62% for systolic blood pressure (SBP) and from 38% to 63% for diastolic blood pressure (DBP).…”
mentioning
confidence: 99%
“…The genetics of ambulatory BP (ABP) may differ, however, because it is unaffected by the "white-coat" effect. 6 The added value of ABP measurements is best illustrated by studies showing that ABP is a better predictor of target organ damage, 7 cardiovascular morbidity, and mortality 8,9 than conventional office BP.…”
mentioning
confidence: 99%